2021
DOI: 10.3390/brainsci11050639
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Posterior Insula in Chronic Pain: A Theoretical Framework

Abstract: Introduction: To date, clinical trials of deep brain stimulation (DBS) for refractory chronic pain have yielded unsatisfying results. Recent evidence suggests that the posterior insula may represent a promising DBS target for this indication. Methods: We present a narrative review highlighting the theoretical basis of posterior insula DBS in patients with chronic pain. Results: Neuroanatomical studies identified the posterior insula as an important cortical relay center for pain and interoception. Intracranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 136 publications
0
24
0
Order By: Relevance
“…pINS is considered the primary interoceptive cortex and plays a crucial role in integrating somatic processing and pain perception [85,[102][103][104]. Further, pINS has been shown to play a role in momentary self-referential processing [105].…”
Section: Discussionmentioning
confidence: 99%
“…pINS is considered the primary interoceptive cortex and plays a crucial role in integrating somatic processing and pain perception [85,[102][103][104]. Further, pINS has been shown to play a role in momentary self-referential processing [105].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the posterior insula is one of the regions most closely related to pain. Electrical stimulation of the posterior insula can cause acute pain, 9 and chronic injury in the posterior insula can lead to neuropathic pain 10 . Also, several VBM studies have shown that the GM of the insular lobe of patients with chronic neuropathic pain is significantly reduced, including trigeminal neuralgia, 11 chronic low back pain, 6 and migraines 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal tracing studies in primates has identified the posterior insula as an important relay in the spinothalamic pathway via connections with the VPM ( 54 57 ). Furthermore, the posterior insula is considered an important cortical center for the integration of pain and interoception ( 54 , 58 – 63 ).…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…In addition to its role as a relay in ascending pain pathways, the posterior insula is densely connected with the anterior insula, which projects to (i) brainstem nuclei involved in the descending pain modulation system (raphe, locus coeruleus, ventral tegmental area, and PAG), and (ii) limbic structures involved in the emotional valence to painful stimuli, such as the ACC and the amygdala ( 61 , 62 , 64 ). Intracranial recordings during painful stimuli have demonstrated the existence of nociceptive neurons in the posterior insula ( 54 , 65 ). In addition, most chronic pain syndromes are associated with abnormal functional connectivity of the posterior insula.…”
Section: Preclinical Modelsmentioning
confidence: 99%